Calcineurin inhibitors in steroid and anti‐TNF‐alpha refractory immune checkpoint inhibitor colitis. Issue 5 (22nd March 2021) - Zhang, Eva; Kiely, Christopher; Sandanayake, Neomal; Tattersall, Stephen
Abstract: Background and Aim: Immune checkpoint inhibitor (ICI) colitis is an increasingly common problem encountered as the use of checkpoint inhibitors (CPIs) grows in the management of cancers. Corticosteroids and tumour necrosis factor (TNF)‐alpha inhibitors are widely recommended in the management of ICI colitis; however, the experience is limited when patients are refractory. Different authors have reported success with vedolizumab, mycophenolate, and cyclosporine. This case series describes our experience with calcineurin inhibitors in the management of corticosteroid and anti‐TNF‐alpha refractory ICI colitis. Methods: Data from electronic medical records were identified and reviewed retrospectively from a cohort of patients treated at a single oncology center. All patients who were identified between March 2018 and May 2020 with ICI colitis refractory to treatment with infliximab and corticosteroids were included. Results: There were 11 patients who developed ICI colitis after receiving CPIs for advanced melanoma and required rescue therapy with either cyclosporine or tacrolimus after treatment failure of infliximab. Median age was 53 (±8.48) years, with nine patients (81%) receiving combination Cytotoxic T‐lymphocyte‐associated protein 4 (CTLA‐4) / programmed cell death protein 1 (PD‐1) immunotherapy. Median time after first CPI infusion to ICI colitis was 4.43 (±19.53) weeks. The median time from onset of symptoms to commencement of rescue therapy with calcineurin inhibitors was 70 days (±66.06). Eight of the 11 patients (72.7%) responded to calcineurin inhibition. In patients who responded, calcineurin inhibitors were continued for a median of 54 (±28.96) days. Conclusion: The calcineurin inhibitors cyclosporine and tacrolimus appear to be a safe and effective option for the management of patients with infliximab‐refractory ICI colitis. The therapeutic benefit is observed rapidly, and adverse effects appear to be limited with close monitoring. Abstract : Immune checkpoint inhibitor (ICI) colitis is an increasingly common and often challenging management problem. In addition to battling prolonged symptoms, colitis may pose a significant interruption to treatment options for malignancy. This case series describes our experience with calcineurin inhibitors in the management of corticosteroid and anti‐TNF‐alpha refractory ICI.